2017
DOI: 10.18632/oncotarget.19458
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of pancreatic adenocarcinoma upregulated factor (PAUF) increases the sensitivity of pancreatic cancer to gemcitabine and 5FU, and inhibits the formation of pancreatic cancer stem like cells

Abstract: Pancreatic cancer stem cells (CSCs) play a crucial role in tumorigenesis and chemoresistance of pancreatic ductal adenocarcinoma. Pancreatic adenocarcinoma up-regulated factor (PAUF), a novel secretory protein, has been shown to contribute to cancer progression and metastasis. Because the clinical relationship between PAUF and pancreatic CSCs is largely unknown, we investigated the associations between the functional role of PAUF and pancreatic CSCs. Pancreatic cancer sphere cultured from the CFPAC-1 cells sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…These alternations result not only in chemotherapeutic efflux from cells, but also accelerate the formation of deoxyribonucleotides from ribonucleotides, which supports proliferation of cancer cells. Moreover, PAUF seems to take part in the activation of transcription of another CSC marker, namely CD133 [165]. In a previous study of this CSC marker, that is CD133, gemcitabine decreased only the viability of CD133-cells at higher concentrations, no therapeutic effects were observed among CD133+ PC cells regardless of the drug concentration used [42,47,53,166].…”
Section: Csc As a Cause Of Resistance To Standard Chemotherapy In Panmentioning
confidence: 89%
See 1 more Smart Citation
“…These alternations result not only in chemotherapeutic efflux from cells, but also accelerate the formation of deoxyribonucleotides from ribonucleotides, which supports proliferation of cancer cells. Moreover, PAUF seems to take part in the activation of transcription of another CSC marker, namely CD133 [165]. In a previous study of this CSC marker, that is CD133, gemcitabine decreased only the viability of CD133-cells at higher concentrations, no therapeutic effects were observed among CD133+ PC cells regardless of the drug concentration used [42,47,53,166].…”
Section: Csc As a Cause Of Resistance To Standard Chemotherapy In Panmentioning
confidence: 89%
“…The latest studies have additionally shown that not only CD44+ PC CSC but also CD24+CD44+ESA+ and CD24+ cells are resistant to gemcitabine [162] [140,163,164]. In these cells there additional mechanisms have been detected for both gemcitabine and 5 fluorouracil resistance related to pancreatic adenocarcinoma up-regulated factor (PAUF), which increased the mRNA expression of multidrug resistant protein 5 (MRP5) and ribonucleotide reductase M2 (RRM2) [165]. These alternations result not only in chemotherapeutic efflux from cells, but also accelerate the formation of deoxyribonucleotides from ribonucleotides, which supports proliferation of cancer cells.…”
Section: Csc As a Cause Of Resistance To Standard Chemotherapy In Panmentioning
confidence: 99%
“…Additionally, they have also revealed that prostate cancer cell sphere formation was markedly suppressed by wild-type p53. Alternatively, Cho et al (26) successfully generated spheres from the adherent pancreatic cancer CFPAC-1 and CAPAN-1 cells bearing p53 mutation in serum-free medium. Based on their observations, CFPAC-1 spheres highly expressed pro-oncogenic PAUF (pancreatic adenocarcinoma upregulated factor) relative to the adherent CFPAC-1 cells and PAUF gene silencing resulted in a decrease in the number of spheres and an enhancement of chemotherapeutic response to GEM in association with downregulation of MRP5 (multidrug resistant protein 5) and RPM2 (ribonucleotide reductase M2).…”
Section: Discussionmentioning
confidence: 99%
“…Chemoresistance is a major hindrance to successful treatment of many tumors. Thus, it is crucial to elucidate the mechanisms of chemoresistance and develop therapeutic strategies to resensitize cancer cells to chemotherapy [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%